Proceso atención de enfermería en paciente adulto con enfermedad renal crónica. - Castro Cevallos, Juleisy Yolanda (2023)
Introduction: Chronic renal failure is a complex clinical and humoral syndrome as an expression of an irreversible condition of renal function, which evolves slowly and progressively, until it reaches the state of terminal uremia, with the complications that it originates in advanced stages. Therefore, it is a disease of great interest and it led me to carry out this clinical case establishing a nursing care plan. Clinical case: it is a 49-year-old patient who was admitted to the emergency area due to presenting a long-standing clinical picture, characterized by myalgia and arthralgia of great intensity, which did not subside with medication, edema in the lower extremities and decreased diuresis, with clinically stable vital signs, which is hospitalized. Regarding the assessment according to theorist Virginia Henderson, several altering needs were found; need to eat and drink properly (he has hyperglycemia). Nursing interventions were carried out where the patient's condition was improved, highlighting the role of the nurse in the education of the patient and also of the relatives who care for him, to whom the health condition was informed. that he presented, his diagnosis, treatment, effects and the correct diet that he had to take due to his health condition.